ASPEK PEMIJAHAN IKAN MOTAN, Thynnichthys thynnoides, BL1EKER1852 (FAMILICYPRINIDAE) DI RAWA BANJIRAN SUNGAI KAMPAR KIRI, RIAU [Spawning aspects of Thynnichthys thynnoides Bleeker 1852 (Family Cyprinidae) in the floodplain of Kampar Kiri River, Riau] - Prawira Atmaja R.P. Tampubolon; M. F. Rahardjo; Djadja S. Sjafei; Charles PH Simanjuntak (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2008)
Study on the spawning aspects of Thynnichthys thynnoides in the floodplain of Kampar Kiri River was conducted from June 2006 to December 2006, using experimental gillnet and trap. Total samples were 852 individuals, comprised 479 individuals from Mentulik (294 males and 185 females) and 373 individuals from Simalinyang (197 males and 176 females). The range of total length was between 94-198 mm for fishes caught from Mentulik and 104-227 mm from Simalinyang. Sex ratio was counted for fishes in QSIIV. Sex ratio is balanced for fish in Mentulik and unbalanced for fish in Simalinyang. The first size of maturity for male in Mentulik and in Simalinyang were 105 and 118 mm; while for female ones were 109 and 108 mm. Presumably, the spawning season is on September-December with the peak spawning in October. Fecundity ranged 781-27135 eggs for fish from Mentulik and 797-35804 eggs from Simalinyang. The Fish is indieaied to be a total spawner.